Secured Energy Aware Projected 5G Network Architecture for Cumulative Performance in Advance Wireless Technologies - Hazem Azez, Hassnen; Sadeq Hussein Ansaf, Hayder; Ali Abdul-Hassan, Hind (International Journal of Engineering and Technology, 2018)
Wireless Networks are known to be susceptible from different energy consumption issues and enormous algorithms are devised so far to improve the lifetime of sensor networks. Low-energy adaptive clustering hierarchy (LEACH) is one of the classical approaches that is adopted in many wireless implementations along with the variants of LEACH to escalate the overall life of nodes as well as network. Underwater Sensor Network or Acoustic Network (UWSN / UWAN) is a type of wireless network that is deployed under the ocean to monitor the movements of enemy or specific corporate purposes. The UWSN are having their base stations at the ships to keep and log the signals from underwater sensor nodes (USN). Such nodes are difficult to track physically and once their lifetime is over because of energy depletion, there is need to redeploy these nodes. To improve the lifetime of such underwater network, a novel and energy efficient approach of population based optimization is used in this research work with integration of soft computing. In this approach, the behavior of the bees in selecting their heads is adopted to form the dynamic cluster head in underwater wireless networks. It is found from the results that the bee colony based energy optimization approach is better as compared to the traditional approach in terms of multiple parameters.Â